Continuous genomic diversification of long polynucleotide fragments drives the emergence of new SARS-CoV-2 variants of concern. Issue 1 (10th March 2022) - Murugadoss, Karthik; Niesen, Michiel J M; Raghunathan, Bharathwaj; Lenehan, Patrick J; Ghosh, Pritha; Feener, Tyler; Anand, Praveen; Simsek, Safak; Suratekar, Rohit; Hughes, Travis K; Soundararajan, Venky
Abstract: Highly transmissible or immuno-evasive SARS-CoV-2 variants have intermittently emerged, resulting in repeated COVID-19 surges. With over 6 million SARS-CoV-2 genomes sequenced, there is unprecedented data to decipher the evolution of fitter SARS-CoV-2 variants. Much attention has been directed to studying the functional importance of specific mutations in the Spike protein, but there is limited knowledge of genomic signatures shared by dominant variants. Here, we introduce a method to quantify the genome-wide distinctiveness of polynucleotide fragments (3- to 240-mers) that constitute SARS-CoV-2 sequences. Compared to standard phylogenetic metrics and mutational load, the new metric provides improved separation between Variants of Concern (VOCs; Reference = 89, IQR: 65–108; Alpha = 166, IQR: 149–181; Beta 131, IQR: 114–149; Gamma = 164, IQR: 150–178; Delta = 235, IQR: 217–255; and Omicron = 459, IQR: 395–521). Omicron's high genomic distinctiveness may confer an advantage over prior VOCs and the recently emerged and highly mutated B.1.640.2 (IHU) lineage. Evaluation of 883 lineages highlights that genomic distinctiveness has increased over time ( R 2 = 0.37) and that VOCs score significantly higher than contemporary non-VOC lineages, with Omicron among the most distinctive lineages observed. This study demonstrates the value of characterizing SARS-CoV-2 variants by genome-wide polynucleotide distinctiveness and emphasizes the need to go beyond a narrow set of mutations at known sites on the Spike protein. The consistently higher distinctiveness of each emerging VOC compared to prior VOCs suggests that monitoring of genomic distinctiveness would facilitate rapid assessment of viral fitness.